2017
DOI: 10.1016/j.snb.2016.07.136
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state synthesis strategy of ZnO nanoparticles for the rapid detection of hazardous Cl2

Abstract: In the present study, rapid and highly efficient solid-state synthesis strategy has been successfully employed for the synthesis of zinc oxide nanoparticles (ZnO NPs). Herein, prepared ZnO NPs are characterized and used for the fabrication of highly sensitive, selective, and accountable gas sensors. Structural elucidation, surface composition, and morphological investigations of as-synthesized ZnO NPs respectively, are carried out using X-ray diffraction, Raman spectroscopy, energy dispersive X-ray spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 38 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…3(a)] has revealed that these flowers are composed of a large number of individual nano-needles clustered together so that they can form the aforementioned Co 3 O 4 micro-dandelions. Such kind of interconnected network of Co 3 O 4 micro-dandelions offers more porosity followed pathways than a dense type surface morphology, as it has a higher surface area to volume ratio, making it more appropriate for gas sensing applications, as higher surface areas maximizes the surface reactions and, consequently, increases the sensor response values [5,21]. In addition, the fluffy nature of the system, having large open spaces existing between the individual nano-needles, permits effortless diffusion of gas molecules into the inner region of the micro-dandelions.…”
Section: Morphological Evolution Studymentioning
confidence: 99%
See 3 more Smart Citations
“…3(a)] has revealed that these flowers are composed of a large number of individual nano-needles clustered together so that they can form the aforementioned Co 3 O 4 micro-dandelions. Such kind of interconnected network of Co 3 O 4 micro-dandelions offers more porosity followed pathways than a dense type surface morphology, as it has a higher surface area to volume ratio, making it more appropriate for gas sensing applications, as higher surface areas maximizes the surface reactions and, consequently, increases the sensor response values [5,21]. In addition, the fluffy nature of the system, having large open spaces existing between the individual nano-needles, permits effortless diffusion of gas molecules into the inner region of the micro-dandelions.…”
Section: Morphological Evolution Studymentioning
confidence: 99%
“…The selectivity bar chart clearly shows that the At 200 °C, these two competing processes are in an optimum level. On the one hand, the H 2 S gas molecules possess sufficient thermal energies to interact with adsorption oxygen species and on the other hand the prevention or the immediate desorption due to excessive thermal energy, thus, sensor reaches to its best response value [5,25,26]. The temperature dependent response study has revealed that the Co 3 O 4 films exhibit its maximum response value to H 2 S @200 °C, therefore 200 °C is considered as an optimized working temperature of the sensor and the same was applied for further studies.…”
Section: Gas Sensing Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The gas sensor recovery was measured by exposing atmospheric air in sensing chamber, confirmed an excellent recovery in just 5 s. The 8/5 s response/recovery time of the WO 3 NBs film sensor represented its ultrafast sensing activity for potential commercial viability. The response/recovery time of gas sensors mainly depends on how quick the gas diffuses in/out [29]. The response/recovery time is an imperative parameter for calculating the gas-sensing performance of a material.…”
Section: Gas Sensing Propertiesmentioning
confidence: 99%